Being Chinese Christian in the Totok Chinese Churches in Surabaya: Continuity and Change of Identities - Linda Bustan; Fatimah Husein; Paulus Sugeng Widjaja (Graduate Program of Pontianak Institute of Islamic Studies, 2020)
This article explores the identities of Chinese Christians in the totok Chinese churches in Surabaya. The Chinese Christians refer to those who arrived in Surabaya from mainland China as Protestant Christians in the 1900s. They established the first Chinese church - the Tiong Hoa Kie Tok Kauw Hwee (THKTKH) in Surabaya. The THKTKH has become two independent synods, namely Gereja Kristus Tuhan (GKT, or the Church of Christ the Lord) and Gereja Kristen Abdiel (GKA, or the Abdiel Christian Church). The totok Chinese churches refer to churches that conduct the church services in the Chinese language or Mandarin (Guoyu). The article examines the culture, language, and origin of the Chinese Christians. After almost a century in Surabaya, there is some continuity and change of the Chinese Christian identity. They still regard themselves as totok, but the meaning of totok has changed. They embrace not only Chinese culture; but also mixed Chinese culture with Western culture and Indonesian culture, which results in the so-called hybrid culture. Mandarin is used in church services, whereas Indonesian language and English are also employed. The originality of the congregations is no longer mono-ethnic, which is Chinese. The Chinese churches have become multi-ethnic churches consisting of various ethnicities in Indonesia.